Experimental contact zones reveal causes and targets of sexual selection in hybridizing lizards. (18th October 2016) - MacGregor, Hannah E. A.; While, Geoffrey M.; Barrett, Jade; Pérez i de Lanuza, Guillem; Carazo, Pau; Michaelides, Sozos; Uller, Tobias
Summary: Divergence in sexually selected traits in allopatry should affect the degree and direction of hybridization. However, few studies have established the causes and targets of sexual selection during secondary contact. Common wall lizards ( Podarcis muralis ) from north‐central Italy have highly exaggerated male sexual traits compared to populations in Western Europe. Using experimental populations, we show that this creates asymmetries in male dominance, spatial habitat use and reproductive success upon secondary contact. Hybridization occurred almost exclusively between males of the Italian lineage and females of the Western European lineage. We provide evidence to suggest stronger ongoing selection on male sexual traits within the dominant Italian lineage. However, these same characters did not predict hybridization, and hybrid matings contributed little to variance in male reproductive success. Instead, most hybrid offspring were sired by Italian males displaying phenotypes associated with lower within‐lineage reproductive success. Thus, highly directional hybridization arises because some Italian males are out‐competed within their own lineage but remain competitive relative to males of the other lineage. This pattern of hybridization is consistent with the direction of introgression in natural contact zones, but our data suggest that sexual selection acting through hybridization may be weak at the leading edge of natural hybrid zones. A lay summary is available for this article. Abstract : Lay Summary